Nitrogen-doping templated nanoporous graphitic nanocage and its supported catalyst towards efficient methanol oxidation - Sheng, Zhao Min (2013)
A unique hollow graphitic nanocage material made up of a few graphitic layers is prepared by using a nitrogen (N)-doping template. The removal of N atoms creates a high density of nanopores on the shells of hollow graphitic nanocages. The prepared N-templated nanocages have a higher specific surface area (595 vs. 530 m2 g− 1) and a much larger mesopore volume (0.72 vs. 0.42 cm3 g− 1) in comparison to the material prepared without the N-doping template. The nanopores on the shell of a N-templated nanocage significantly increase the utilization of its hollow structure for loading catalysts to provide more reaction electro-active sites while promoting molecule diffusion across the shell, making it an excellent material to support PtRu catalysts towards efficient methanol oxidation, which is superior to regular graphitic nanocage supported PtRu and the commercial PtRu/C with the same amount of PtRu loading.